Toxicity induced by concentrations of sucralose, Acesulfame K. and their mixtures on Poecilia reticulata (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
The increased consumption of artificial sweeteners such as sucralose (SUC) and acesulfame-K (ACE-K) has raised concerns due to their presence in aquatic environments and potential ecotoxicological effects, posing a challenge to SDGs 6 and 12. This study aimed to estimate mortality rates and toxic effects induced by environmentally relevant concentrations of SUC, ACE-K, and their mixtures on Poecilia reticulata. Following OECD guideline #203, organisms were exposed for 96 hours to different treatments while behavioral responses were monitored. The results revealed significant temporal toxicity patterns, including hyperactivity, hypoactivity, abnormal surface and bottom behaviors, and a high incidence of abnormal feces, with exposure time being a critical factor. It was concluded that these sweeteners induced complex behavioral alterations in P. reticulata, highlighting their potential risk as emerging contaminants and emphasizing the need for multi-level toxicity assessments (cellular, tissue, embryological) in future studies.